Growth patterns and environmental adaptions of the tree species planted for ecological remediation in typhoon-disturbed areas—A case study in Zhuhai, China - Zhang, Chi; Qian, Wanhui; Song, Lei; Zhao, Qing (Frontiers in Sustainable Cities, 2022)
Typhoon frequently results in various mechanical damages to urban forest ecosystems. Imperative forest remediation projects were launched to restore the environmental conditions in cities, in which massive trees were newly planted. However, it was rarely answered whether the newly planted trees could acclimate to typhoon circumstances and enhance the wind resistance of the local ecosystem. Therefore, it was necessary to achieve information on the physical growth and windy environmental adaption of newly planted trees, which could promote a profound understanding of the efficiency of post-typhoon ecological remediation. In this study, we selected Zhuhai's urban-forest remediation district as our research area that suffered severely from Typhoon Hato (2017). The six newly-planted tree species for the ecological remediation were measured for their above- and below-ground processes from June 2018 to December 2019, including their development of tree height, ground diameter, crown size, and fine root biomass. Additionally, the variations of the soil's physical and chemical properties were also measured to assess the impact of plantation on soil conditions. Our results showed that the six surveyed tree species had different above- and below-ground growth patterns. With robust root development at horizontal and vertical levels combined with relatively short and thick above-ground profiles, Sterculia lanceolata Cav. and Cinnamomum camphora (Linn) were likely to cope well with typhoon disturbances. Ilex rotunda Thunb. and Schima superba Gardn. et Champ. exhibited moderate acclimation to windy environment, while Elaeocarpus sylvestris (Lour.) Poir. and Elaeocarpus apiculatus Mast. were not recommended to be planted in typhoon-disturbed areas concerning their unstable root development. In addition, the ecological remediation did improve the soil properties, specifically for the chemical characteristics including available nitrogen, available potassium, and soil organic matter. To improve the effectiveness of forest remediation in the future, it was better to choose those tree species with vigorous root development and steady values of root:shoot ratios, which might be advantageous for coping with typhoon disturbances. The tree species with prosperous above-ground growth were not suitable for areas facing strong winds directly but could be planted in leeward regions to amplify their landscape functions.